Effect of CAPN3 gene genotypes on productive traits and carcass traits of broiler - Iman Abdul Amir Thbit; Ali A. Abdulkareemm; Abdullah Hameed Salim (University of Thi-Qar Journal of agricultural research, 2021)
Determining the genotypes of the CAPN3 gene and studying its relationship to some economic characteristics of broiler chickens, which included weekly weights, final live weight, carcass weight and carcass parts weights, in addition to the correlation coefficient for some important Ross characteristics. 308 chickens, in which 100 chicks were bred for 35 days and taken. Primary birds were weighed and all birds were numbered. Genotypes were determined by analyzing the nitrogenous base sequences of the studied part of the CAPN3 gene the site of variation in the nitrogenous bases of the studied gene (G>C2426) was diagnosed and the resulting genotypes were calculated, which are three genotypes: GG, GC, and CC of the CAPN3 gene. As for the CAPN3 gene, the results showed statistically significant differences for some traits such as chest weight and wing weight, while the results did not indicate any statistically significant differences between the three models for other traits such as live body weight, carcass, and thigh weight, back weight, weekly weights, and superiority of genotype CC on the rest of the individuals in some traits. the study suggests the possibility of using molecular markers of the CAPN3 gene in poultry breeding and selection programs.